OPTIMIZATION OF Bacillus paramycoides FERMENTATION MEDIUM TO INCREASE THE PRODUCTION OF 5-AMINOLEVULINIC ACID IN A 10 LITER FERMENTER - Monconegoro, Dicky Adihayyu (BRIN - Badan Riset dan Inovasi Nasional, 2022)
5-Aminolevulinic acid is an essential precursor for the biosynthesis of tetrapyrrole compounds, such as chlorophyll and heme. 5-ALA has the potential to be used as a plant growth and antioxidant activity enhancer. 5-ALA can be produced through fermentation by Bacillus paramycoides. This study aimed to optimize B. paramycoides fermentation medium to increase 5-ALA production. The optimization was carried out using response surface method (RSM) experimental design. 5-ALA production in a 10 L fermenter was conducted using an optimized medium and supplemented with MSG as a precursor and wood vinegar as an inhibitor. The results showed that the best medium composition was 27.78 g L-1 molasses; 9.145 g L-1 urea; 8.838 g L-1 NaCl; and 32.07 g L-1 glucose, resulting in 10.749 (log CFU mL-1) and 255.30 µM 5-ALA. 5-ALA production trial in a 10 L fermenter produced 581.82 µM 5-ALA. Medium optimization and precursor-inhibitors addition in the fermentation increased the 5-ALA yield 3.2 times compared to before optimization.